2019
DOI: 10.1002/ped4.12136
|View full text |Cite
|
Sign up to set email alerts
|

Central precocious puberty as a prelude to hypogonadism in a patient with Klinefelter syndrome

Abstract: Introduction Incomplete pubertal development is a common phenomenon found in patients with Klinefelter syndrome (KFS). KFS combined with central precocious puberty (CPP) rarely occurs. We herein report a rare case of KFS with CPP and review several studies to determine the possible mechanism underlying this condition. Case presentation An 8‐year, 5‐month‐old male patient was admitted to our hospital because of enlargement of the penis and small testes. Laboratory evaluation revealed high luteinizing hormone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In fact, some patients with chromosomal DSD also presented precocious puberty. Chunxiu Gong et al [ 27 ] reported a rare case of Klinefelter syndrome (KS) with CPP and performed a review of the literature that showed different cases in which precocious sex development was found in KS, Turner Syndrome, and congenital adrenal hypoplasia. Some KS cases had abnormal productions of human chorionic gonadotropin via endocrine tumors as pathogenic elements of peripherical precocious puberty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, some patients with chromosomal DSD also presented precocious puberty. Chunxiu Gong et al [ 27 ] reported a rare case of Klinefelter syndrome (KS) with CPP and performed a review of the literature that showed different cases in which precocious sex development was found in KS, Turner Syndrome, and congenital adrenal hypoplasia. Some KS cases had abnormal productions of human chorionic gonadotropin via endocrine tumors as pathogenic elements of peripherical precocious puberty.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that early activation of the HPG axis may result in CPP and subsequent hypogonadism, due to premature gonadal cell apoptosis, in patients with KS. GnRH agonist therapy allows the suppression of the HPG axis to treat precocious puberty and protect against premature gonadal insufficiency [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] Our recently published studies pointed out that CPP may serve as a prelude to hypogonadism. [ 15 ] In all published papers on MKRN3 till now, only Grandone et al [ 16 ] reported a CPP case harboring the MKRN3 mutation (Pro160Cysfs ∗ 14) presented with the POF (premature menopause at 36 yrs). Therefore, a long-term clinical follow-up is necessary for our present case to evaluate the possible association between MKRN3 mutations and POF.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of selective Sertoli cell failure and/or lack of germ cells, testicular volume usually remains small although testosterone production may be active. Boys with partial hypogonadism may also show signs of precocious puberty (173,174).…”
Section: Rationalementioning
confidence: 99%